(untitled) (Quinto Sol, 2020)
Traditionally, studies referring to the Human Rights Movement in Argentina focused on a group of organizations that resisted the last military dictatorship (1976-1983), detached from the political struggles of the past. In general, an issue that has been scarcely addressed is the link between contemporary political parties and the issue of human rights. In this article I examine the links generated by one of these parties with the Human Rights Movement as a political space of reference: the Partido Comunista Revolucionario, in the regional space of the province of Santa Fe, paying special attention to the city of Rosario.